2019
DOI: 10.5530/ijcep.2018.6.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Sympathovagal Imbalance and Cognitive Deficit in Postmenopausal Women: A Mini Review

Abstract: Menopause is a Greek word meaning, 'meno'-month, 'pause'-ceases. Menopausal transition includes autonomic dysfunctions like somatic symptoms, vasomotor symptoms and mental disturbances such as mood changes, depression, irritability, forgetfulness and lack of concentration that decreases the quality of life. These climacteric vasomotor symptoms are due to alteration of autonomic hemodynamic regulation. Recently, there developed a concept of increased cardiovascular risk and mortality in individuals with sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[4] It is found that there is a decline in heart rate variability in post-menopausal women. [5] Recent study shows that post-menopausal state also offers higher risk of developing metabolic syndrome with an increased level of insulin resistance. [6] This can also be indicated by deranged lipid profile in them, such as higher triglyceride and total cholesterol.…”
mentioning
confidence: 99%
“…[4] It is found that there is a decline in heart rate variability in post-menopausal women. [5] Recent study shows that post-menopausal state also offers higher risk of developing metabolic syndrome with an increased level of insulin resistance. [6] This can also be indicated by deranged lipid profile in them, such as higher triglyceride and total cholesterol.…”
mentioning
confidence: 99%